2017
DOI: 10.1002/pits.22033
|View full text |Cite
|
Sign up to set email alerts
|

Protective factors for depressive symptoms in adolescents: Interpersonal relationships and perceived social support

Abstract: The association between interpersonal relationships, perceived social support, and depressive symptoms in adolescents was investigated in the present study. The Center for Epidemiologic Studies Depressive Symptoms Scale (CES-D-SF), Multidimensional Scale of Perceived Social Support (MSPSS), and Interpersonal Relationship Scale (IRS) were administered to 1,573 high school students. There were four main findings: all three types of interpersonal relationships (same-sex peer, opposite-sex peer, and teacher-studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…In order to provide empirical bases for intervention and treatment of depressive symptoms, this study integrates these three variables and attempts to explore the potential psychological mechanisms behind them. In addition, because previous research suggested that both grade and sex may significantly affect parental attachment (Chen et al, ), expressive suppression (Dong & Zhang, ), and depressive symptoms (Cui, Shi, Zhang, & Yu, ; Fredrick, Demaray, Malecki, & Dorio, ; Luo, Xiang, Zhang, & Wang, ), we included these two variables as covariates in our data analyses. Therefore, based on the above literature review, we examined the relationships between parental attachment, emotion regulation (expressive suppression and cognitive reappraisal), and depressive symptoms among Chinese adolescents.…”
mentioning
confidence: 99%
“…In order to provide empirical bases for intervention and treatment of depressive symptoms, this study integrates these three variables and attempts to explore the potential psychological mechanisms behind them. In addition, because previous research suggested that both grade and sex may significantly affect parental attachment (Chen et al, ), expressive suppression (Dong & Zhang, ), and depressive symptoms (Cui, Shi, Zhang, & Yu, ; Fredrick, Demaray, Malecki, & Dorio, ; Luo, Xiang, Zhang, & Wang, ), we included these two variables as covariates in our data analyses. Therefore, based on the above literature review, we examined the relationships between parental attachment, emotion regulation (expressive suppression and cognitive reappraisal), and depressive symptoms among Chinese adolescents.…”
mentioning
confidence: 99%
“…Some studies have however showed that low social support was related to higher levels of depressive symptoms to a greater extent among females, than males [24,25]. The results from the literature show that different social relationships and forms of social support have different impact on mental health among males and females [26,27]. For young women, friendships with other young women had the strongest social support effect on depressive symptoms, whereas for young men, the support of their teacher had the strongest effect [26].…”
Section: The Role Of Protective Factors For Mental Healthmentioning
confidence: 97%
“…The results from a large review study, showed that social support was a signi cant protective variable for depression among both young males and females [23]. Another study by Luo et al from 2017 [26] showed that different social relationships had different impact on mental health among males and females. For girls, same-sex friendships had the strongest social support effect on depressive symptoms, whereas for boys, teacher-student relationships did.…”
Section: Social Support and Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…Acceptance from peers is an important element for adolescents and without it, they may develop psychological and social development disorders. According to Berndt & Perry, althy view of themselves, undergo school education well, are able to get along, and have a small chance to behave aggressively, Interpersonal Relationships of students in Junior High School Conversely, adolescents with low interpersonal relationships feel lonely (Michek & Loudová, 2014;Zhang, Gao, Fokkema, Alterman, & Liu, 2015), anxious (Lasgaard, Goossens, Bramsen, Trillingsgaard, & Elklit, 2011), depressed (Kenny et al, 2013;Luo, Xiang, Zhang, & Wang, 2017), having difficulty adjusting to the school environment and getting along with their friends (Tirmidzi, Nursalim, Pratiwi, & Setiawati, 2013;Bagwell, Kochel, & Schmidt, 2015). This leads to conflicts, hostility (Burk& Laursen, 2005), anti-social behaviors such as aggressiveness and fighting (Santrock, 2014), and disrupt the learning process in school (Collie et al, 2016).…”
Section: International Journal Of Research In Counseling and Educationmentioning
confidence: 99%